Establishing an Anaesthesia and Intensive Care partnership and aiming for national impact in Tanzania. Issue 1 (December 2016) - Ulisubisya, Mpoki; Jörnvall, Henrik; Irestedt, Lars; Baker, Tim
Abstract Anaesthesia and Intensive Care is a neglected specialty in low-income countries. There is an acute shortage of health workers – several low-income countries have less than 1 anaesthesia provider per 100, 000 population. Only 1.5 % of hospitals in Africa have the intensive care resources needed for managing patients with sepsis. Health partnerships between institutions in high and low-income countries have been proposed as an effective way to strengthen health systems. The aim of this article is to describe the origin and conduct of a health partnership in Anaesthesia and Intensive Care between institutions in Tanzania and Sweden and how the partnership has expanded to have an impact at regional and national levels. The Muhimbili-Karolinska Anaesthesia and Intensive Care Collaboration was initiated in 2008 on the request of the Executive Director of Muhimbili National Hospital in Dar es Salaam. The partnership has conducted training courses, exchanges, research projects and introduced new equipment, routines and guidelines. The partnership has expanded to include all hospitals in Dar es Salaam. Through the newly formed Life Support Foundation, the partnership has had a national impact assisting the reanimation of the Society of Anaesthesiologists of Tanzania and has seen a marked increase of the number of young doctors choosing a residency in Anaesthesia and Intensive Care.